A Case Study on A University-Community Partnership to Eliminate Racial Disparities in Infant Mortality: Effective Strategies and Lessons Learned. Issue 8 (17th November 2019) - Cotton, Quinton D.; Smith, Pamela; Ehrenthal, Deborah B.; Green-Harris, Gina; Kind, Amy J.H.
ABSTRACT: This case study discusses the implementation framework, effective strategies, and lessons learned of a university-community partnership addressing racial disparities in infant mortality. The partnership was successful at enhancing coordination within service delivery systems for maternal and child health programs. Results: the elimination of waiting list for services, maximizing federal and state reimbursement, the adoption of culturally-appropriate intervention practices, increasing racial diversity in the workforce, diffusing silos, and facilitating healthier relationships among service providers. Key lessons: activating the collective strengths among a network of diverse community stakeholders with shared interests, prioritizing black voices in the change process, and capacity building opportunities.